Optical transitions in GaInNAs/GaAs multiquantum wells with varying N contents investigated by photoluminescence excitation spectroscopy - Sun, Handong (2009)
We report on the nitrogen-concentration dependence of optical transitions between quantized states of electrons and holes in GaInNAs/GaAs multi-quantum wells. Using low-temperature photoluminescence excitation spectroscopy, systematic studies have been performed on a series of samples with nitrogen concentrations in the range 0%–1.14%. The observed data were compared with theoretical fitting based on the band anticrossing model in which the localized N states interact with the extended states in the conduction band, taking strain effects into account. Our results are consistent with the band anticrossing model, but with differing coupling strength between different quantum states of electrons in the quantum wells.